Identifikasi dan siklus hidup chydoridae (Cladocera) di Perairan Sulawesi Utara - Pangkey, Henneke; Monijung, Revol D.; Mantiri, Rose; Lantu, Sartje (e-Journal BUDIDAYA PERAIRAN, 2018)
The purpose of this study was to identify chydoridae using conservative way, while the observations of the life cycle was done through a microscope to determine the egg production per parent and length of life. Individual chydoridae acclimatized to reach 10 generations (1 month), and 10 females were isolated for the production of seedlings. Based on literatures review, chydoridae used was derived from subfamily Aloninae (Alona spp.); while studies on the life cycle found: the egg size of chydoridae 150.2 ± 22.4 μm, and neonates have an average size of 291.82 ± 3.06 μm, and reached adult size after 2.3 ± 0.5 days, with an average size of 441.22 ± 10.2 μm. Time of embryonic development occured for 1-2 days. On the entire life cycle, only 2 eggs could be produced per individual. Based on this study, the number of eggs produced by the female during its lifetime ranges between 30-60 eggs. Similarly, the length of life of this organism on average 47.2 ± 11.7 days, with the longest lifespan was achieved 60 days. It was found also the maximum size was 1,037 ± 8.5 mm; while the average size of an organism's body was 800.42 ± 56.3 μm.Keywords: chydoridae, identification, life cycle, Alona spp